2012
DOI: 10.1111/j.1469-185x.2012.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of biotic interactions in shaping distributions and realised assemblages of species: implications for species distribution modelling

Abstract: Predicting which species will occur together in the future, and where, remains one of the greatest challenges in ecology, and requires a sound understanding of how the abiotic and biotic environments interact with dispersal processes and history across scales. Biotic interactions and their dynamics influence species' relationships to climate, and this also has important implications for predicting future distributions of species. It is already well accepted that biotic interactions shape species' spatial distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
1,288
4
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,392 publications
(1,388 citation statements)
references
References 157 publications
33
1,288
4
6
Order By: Relevance
“…For example, overstorey density directly affects both litter depth and shading, and we cannot readily separate their effects on plant performance. Despite these limitations, the multiple analysis approaches we employed suggested that several biotic variables have significant direct and indirect effects, which supports the growing evidence that biotic interactions can strongly affect plant distributions across abiotic gradients (Wisz et al, 2013). Overall, our results highlight how biotic conditions and soil fertility are strongly associated with regional distribution patterns and may interact with climate-related variables (e.g.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…For example, overstorey density directly affects both litter depth and shading, and we cannot readily separate their effects on plant performance. Despite these limitations, the multiple analysis approaches we employed suggested that several biotic variables have significant direct and indirect effects, which supports the growing evidence that biotic interactions can strongly affect plant distributions across abiotic gradients (Wisz et al, 2013). Overall, our results highlight how biotic conditions and soil fertility are strongly associated with regional distribution patterns and may interact with climate-related variables (e.g.…”
Section: Discussionsupporting
confidence: 59%
“…Models with biotic conditions alone were able to significantly distinguish presence from absence points, while models with topographic microclimate and/or soil fertility alone only weakly differentiated them (P-values close to 0Á05, Table 3). These results suggest that inclusion of biotic conditions may significantly improve distribution model predictions in space and time (Wisz et al, 2013), although the relative contribution of biotic conditions to distribution is likely to vary with species tolerance to disturbance and environmental stress (Meier et al, 2010). The strength of biotic conditions compared to abiotic factors in our models suggests that changes in biotic factors could significantly alter distribution patterns with respect to abiotic factors.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Even though biotic interactions have generally been considered to be unimportant in determining large-scale distributions (for a review see Wisz et al 2013), they have recently been suggested to affect species distributions and plant assemblages at regional, continental and global scales (Hampe and Jump 2011;Wisz et al 2013). Thus, biotic interactions ought to be considered in management practices of Z. abelicea.…”
Section: Probability Of Occurrence and Biotic Interactionsmentioning
confidence: 99%
“…Similarly, we can quantify the relative vulnerability of local species of concern to pathogen spillover from these same introduced species. Models to predict the future distribution of plant invasions have been constrained by the difficulty of incorporating biotic drivers, including pathogens and parasites 30 . We show how fairly simple information on the species composition of resident plant communities could help predict both variation in the spread of an invasive species across a landscape and variation in the impact of that species.…”
mentioning
confidence: 99%